2019
DOI: 10.1002/aelm.201800904
|View full text |Cite
|
Sign up to set email alerts
|

The Thermoelectric Properties of Bismuth Telluride

Abstract: Bismuth telluride is the working material for most Peltier cooling devices and thermoelectric generators. This is because Bi2Te3 (or more precisely its alloys with Sb2Te3 for p‐type and Bi2Se3 for n‐type material) has the highest thermoelectric figure of merit, zT, of any material around room temperature. Since thermoelectric technology will be greatly enhanced by improving Bi2Te3 or finding a superior material, this review aims to identify and quantify the key material properties that make Bi2Te3 such a good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
456
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 556 publications
(476 citation statements)
references
References 209 publications
(325 reference statements)
18
456
2
Order By: Relevance
“…The present thermoelectric performance of halide perovskites is significantly lower than the state‐of‐the‐art inorganic thermoelectric materials such as Bi 2 Te 3 , Cu 2 S, SnSe, lead chalcogenides where the ZT value is generally higher than 1. [ 120–123 ] In the case of organics and hybrids, their best ZT values lie between 0.4–0.6. [ 124–126 ] The current highest ZT for halide perovskites is in the range ≈0.1.…”
Section: Halide Perovskites Based Thermoelectricsmentioning
confidence: 99%
“…The present thermoelectric performance of halide perovskites is significantly lower than the state‐of‐the‐art inorganic thermoelectric materials such as Bi 2 Te 3 , Cu 2 S, SnSe, lead chalcogenides where the ZT value is generally higher than 1. [ 120–123 ] In the case of organics and hybrids, their best ZT values lie between 0.4–0.6. [ 124–126 ] The current highest ZT for halide perovskites is in the range ≈0.1.…”
Section: Halide Perovskites Based Thermoelectricsmentioning
confidence: 99%
“…There has therefore been significant effort devoted to alternative systems including the more earth-abundant SnS [2] and metal oxides [7][8][9][10].Alloying is commonly used as a means to enhance thermoelectric performance, as a suitable choice of components can maintain or improve a favourable electronic structure while reducing k latt by introducing variation in atomic masses and chemical bond strength to promote stronger phonon scattering [11]. Pb(S, Se, Te), Sn(S, Se) and (Bi, Sb) 2 (Se, Te) 3 alloys have all been studied as thermoelectrics and the alloying shown to improve ZT [12][13][14][15][16][17]. Due to the record-breaking high-temperature ZT of SnS, the Te-free Sn(S, Se) alloys are of particular interest, and experimental studies have demonstrated a reduction in the thermal conductivity of mixed compositions [12,14].Thermoelectricity is unique in that all four of the terms in the figure of merit ZT are amenable to calculation using first-principles electronic-structure methods such as density-functional theory (DFT) [18].…”
mentioning
confidence: 99%
“…Alloying is commonly used as a means to enhance thermoelectric performance, as a suitable choice of components can maintain or improve a favourable electronic structure while reducing k latt by introducing variation in atomic masses and chemical bond strength to promote stronger phonon scattering [11]. Pb(S, Se, Te), Sn(S, Se) and (Bi, Sb) 2 (Se, Te) 3 alloys have all been studied as thermoelectrics and the alloying shown to improve ZT [12][13][14][15][16][17]. Due to the record-breaking high-temperature ZT of SnS, the Te-free Sn(S, Se) alloys are of particular interest, and experimental studies have demonstrated a reduction in the thermal conductivity of mixed compositions [12,14].…”
mentioning
confidence: 99%
“…The κ of bismuth telluride can also be minimized by microstructure engineering and nanostructuring. [ 88–91 ] Bi 2 Te 3 materials are already used in thermoelectric refrigeration, TEGs, and thermal sensors. [ 92,93 ]…”
Section: Use Of Wastes In the Synthesis Of Te Materialsmentioning
confidence: 99%